Vection Is Enhanced by Increased Exposure to Optic Flow. (May 2018) - Seno, Takeharu; Murata, Kayoko; Fujii, Yoshitaka; Kanaya, Hidetoshi; Ogawa, Masaki; Tokunaga, Kousuke; Palmisano, Stephen
We examined whether vection strength could be modulated by altering the exposure duration to optic flow. Experiment 1 sourced 150 different video clips from various Japanese animation works which simulated self-motion. Despite large differences in the content of these video clips, we found a significant positive correlation between their play durations and their ratings of vection magnitude. Experiment 2 examined this relationship further using more tightly controlled visual motion stimuli. Vection was induced by presenting the motion of the same expanding grating stimulus for 8, 16, 32, or 64 seconds. While vection onset latencies remained constant across these four conditions, vection magnitude/strength was found to increase systematically with the exposure duration. As predicted by a recent computational model of vection, we conclude that subjective vection strength does depend on the exposure duration to optic flow.